Linked Open Corpus Models, Leveraging the Semantic Web for Adaptive Hypermedia - LAWLESS, SEAMUS; O'KEEFFE, IAN; WADE, VINCENT PATRICK; O'CONNOR, ALEXANDER (ACM, 2012)
Despite the recent interest in extending Adaptive Hypermedia beyond the closed corpus domain and into the open corpus world of the web, many current approaches are limited by their reliance on closed metadata model repositories. The need to produce large quantities of high quality metadata is an expensive task which results in silos of high quality metadata. These silos are often underutilized due to the proprietary nature of the content described by the metadata and the perceived value of the metadata itself. Meanwhile, the Linked Open Data movement is promoting a pragmatic approach to exposing, sharing and connecting pieces of machine-readable data and knowledge on the WWW using an agreed set of best practices. In this paper we identify the potential issues that arise from building personalization systems based on Linked Open Data.
The 23rd ACM Conference on Hypertext and Social Media, HT 2012
PUBLISHED
Milwaukee, WI, USA
Keywords: Adaptive Hypermedia; Linked Open Data